Historical Basis And Present Status Of Professional Training Of Technology Teachers - Zaripov Lochin Rustamovich (Peerian Journals Publishing, 2024)
This article presents the theoretical conditions for increasing the professional competence of future technologists, the role and place of the science of “technology” in the general education system, and trends in its development in its paradigms. The history and aspects of the professional training of future technologists are also considered, as well as the development of technological literacy, critical, creative and systematic thinking, the ability to make independent decisions, the ability to demonstrate their intellectual abilities, the formation of moral qualities, mature individuals information is provided.
Keywords: Technological literacy; critical; creative